The Idioms Described in the Fiction Luk sao khong phak of Souvanhthone Bouphanouvong - PHENGPHANYA, Phone; MANIVONG, Phim; Zhengli, Shang; VANHVILAI, Finhxiaw (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
In this research project, the researchers aimed to study of the idioms that described in fiction “Louk sao khong phak” of Suvanthone Bouphanouvong" or Daughter of Party by following the aim of analyzing the idioms’ description of the fictional characters. This was a qualitative consisted. The instrument used for this study was a questionnaire consisted of 19 items to find the Idioms that described the character shape by explaining, proving and interpreting the comparative idioms. The results of this study found that the appearance description of the fictional characters were 19 idioms, such as; comparing the appearance of a thin tall person, face a person with a tomato, face of a person with an egg, eyes of a person to pigeon eyes, person to a person with big picture, face like an egg, the beauty like rose, the forehead to the size and the appearance of eyes, the shape of a short person to a single claw of tamarind, a big cheek like a fat pig, a small face like monkey, a big stomach like pregnancy, the shape of a person to a tall awesome person, the beautiful legs like elephant ivory, the fingers to larva, white face like peeled egg, the lips like lotus, the people skin to the sun, and the people face like flowers.